موقف الإسلام من العصبية القبلية وتطبيقاته على الواقع الصومالي: Islamic Position on Tribalism and Its Applications to the Somali Context - Hussein Said, Abdukafi; Abdulrahman, Manswab Mahsen (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
ملخص البحث يتناول هذا البحث موضوع موقف الإسلام من العصبية القبلية وتطبيقاته على الواقع الصومالي، مبينًا الأسس الشرعية التي أرساها الإسلام في تنظيم العلاقة بين الانتماء القبلي ومبدأ الأخوّة الإيمانية. ويهدف إلى بيان الفرق بين الانتماء القبلي المشروع بوصفه رابطة تعارف وتكافل، وبين العصبية المذمومة التي تقوم على الظلم ونصرة الباطل والتعصب الأعمى. اعتمد البحث على المنهج الاستقرائي التحليلي من خلال استقراء النصوص الشرعية من القرآن الكريم والسنة النبوية، مع الاستئناس بأقوال الفقهاء والمفسرين، ثم تنزيل تلك القواعد على الواقع الصومالي المعاصر. وقد خلص إلى أن الإسلام لا يرفض الانتماء القبلي في ذاته، وإنما يهذّبه ويضبطه بضوابط العدل والتقوى، مستندًا إلى قوله تعالى في القرآن الكريم: ﴿يَا أَيُّهَا النَّاسُ إِنَّا خَلَقْنَاكُم مِّن ذَكَرٍ وَأُنثَىٰ وَجَعَلْنَاكُمْ شُعُوبًا وَقَبَائِلَ لِتَعَارَفُوا﴾، وإلى قول النبي ﷺ: "ليس منا من دعا إلى عصبية". كما بيّن البحث أن العصبية القبلية حين تتحول إلى أداة للصراع السياسي، أو وسيلة للإقصاء الاجتماعي، أو سببًا لإشعال النزاعات المسلحة – كما هو الحال في بعض مراحل التاريخ الحديث في الصومال – فإنها تُعد مخالفة صريحة لمقاصد الشريعة في حفظ الدين والنفس والمال ووحدة الأمة. وانتهى البحث إلى جملة من النتائج، أبرزها: ضرورة تعزيز الهوية الإسلامية الجامعة، وتفعيل دور العلماء والدعاة في تصحيح المفاهيم، وإدماج القيم الشرعية في مؤسسات التعليم والإعلام، والعمل على بناء نظام اجتماعي وسياسي يقوم على مبدأ المواطنة العادلة بدل المحاصصة القبلية، بما يسهم في تحقيق السلم الأهلي والاستقرار المجتمعي في الواقع الصومالي. ABSTRACT This study examines Islam’s position on tribalism and its applications to the Somali context, clarifying the Islamic foundations that regulate the relationship between tribal affiliation and the principle of Islamic brotherhood. It aims to distinguish between legitimate tribal belonging—considered a bond of social recognition and mutual support—and blameworthy tribalism based on injustice, blind loyalty, and support for falsehood. The research adopts an inductive and analytical approach by examining relevant Qur’anic verses and Prophetic traditions, alongside the opinions of jurists and exegetes, and then applying these principles to the contemporary Somali context. The study concludes that Islam does not reject tribal affiliation in itself; rather, it refines and regulates it according to the principles of justice and piety. This is grounded in the verse of the Qur’an: “O mankind, indeed We created you from male and female and made you peoples and tribes that you may know one another” (49:13), and in the Prophet’s statement: “He is not one of us who calls to tribalism.” The study further demonstrates that when tribalism becomes a tool for political conflict, social exclusion, or armed violence—as witnessed in certain periods of modern history in Somalia—it clearly contradicts the objectives of Islamic law (maqāṣid al-sharīʿah), particularly the preservation of religion, life, property, and communal unity. The paper concludes with several key recommendations, including strengthening a unified Islamic identity, enhancing the role of scholars and preachers in correcting misconceptions, integrating Islamic ethical values into educational and media institutions, and promoting a just citizenship-based system rather than clan-based power-sharing, in order to foster social peace and stability in the Somali context.